Financial shenanigans : how to detect accounting gimmicks and fraud in financial reports - Schilit, Howard Mark, 1952-; Perler, Jeremy; Engelhart, Yoni (McGraw-Hill Education, 2018)
Shining a light on the most shocking frauds and financial reporting offenders, this unparalleled guide gives investors the tools they need to spot deceptive financial reporting in the global markets. --